2010
DOI: 10.2131/jts.35.757
|View full text |Cite
|
Sign up to set email alerts
|

Testicular spermiation failure in rats exposed prenatally to 3,3',4,4',5-pentachlorobiphenyl

Abstract: -Testicular spermatogenesis was studied in 7-, 10-, 13-and 17-week-old Sprague-Dawley rats whose dams had been administered intragastrically with 2.5, 25, or 250 ng of 3,3′,4,4′,5-pentachlorobiphenyl (PCB126) or vehicle on days 13-19 of gestation. The 250 ng groups among the 7-, 10-and 13-week-old offspring showed significant inhibition of mature spermatid release (spermiation), but 17-weekold offspring did not show this. These alterations were not observed in other PCB126 and vehicle groups, and no germ cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Regarding DL‐PCBs, and contrary to experimental animals (e.g. Wakui et al., , see Annex A.5), there is no conclusive evidence based on humans studies. The CONTAM Panel noted the uncertainty in relation to the association with PCDF exposure, but other studies on semen quality in relation to high PCDF exposure, e.g.…”
Section: Assessmentmentioning
confidence: 95%
“…Regarding DL‐PCBs, and contrary to experimental animals (e.g. Wakui et al., , see Annex A.5), there is no conclusive evidence based on humans studies. The CONTAM Panel noted the uncertainty in relation to the association with PCDF exposure, but other studies on semen quality in relation to high PCDF exposure, e.g.…”
Section: Assessmentmentioning
confidence: 95%
“…PCB exposure studies have demonstrated conflicting relationships with male hormones in both animal (Wakui et al 2010; Xiao et al 2011; Xu et al 2013; Zhu et al 2013) and human studies. For example, in a cohort of boys with higher prenatal exposure to PCBs during the Yucheng incident in 1978–79 (n=47) and unexposed controls (n=49), exposed boys who were at puberty (≥13 years old) had lower T levels and higher estradiol and FSH levels (non-significant) compared to controls, but there was no difference in boys < 13 years; there were also no differences in LH levels (Hsu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The studies were conducted in rats, mice or goats. We identified four studies examining the effects of PCB-77 [ 39 42 ], two studies on those of PCB-118 [ 43 , 44 ], four studies which looked at PCB-126 [ 39 , 45 47 ], two studies for PCB-132 [ 48 , 49 ], one study for PCB-149 [ 48 ], two studies reporting on PCB-153 [ 45 , 50 ], two on PCB-169 [ 51 , 52 ] and one report on PCB-180 [ 53 ]. All these studies were selected for the data extraction process.…”
Section: Resultsmentioning
confidence: 99%
“…There were four studies of PCB-126, of which one was conducted in goats [ 45 ] and the other three in rats [ 39 , 46 , 47 ]. The goat study and two of the rat studies were rated at an overall confidence level of “ High ” ( TIER 1 ) due to all elements being evaluated as “definitely low” or “probably low risk” [ 45 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation